Guselkumab improves work productivity in patients with moderate-to-severe psoriasis with or without depression and anxiety: results from the VOYAGE 2 comparator study versus adalimumab. (17th August 2020) - Reich, Kristian; Foley, Peter; Han, Chenglong; McElligott, Sean; Muser, Erik; Li, Nan; Armstrong, April W.
Abstract: Purpose: To evaluate the impact of guselkumab on work productivity, including absenteeism and presenteeism, in psoriasis patients with and without depression/anxiety. Methods: VOYAGE 2 is a randomized, double-blind, placebo-controlled, and comparator-controlled, phase 3 trial that compared guselkumab with adalimumab in patients with moderate-to-severe psoriasis. Absenteeism was evaluated among patients who reported that their skin prevented work/study based on the Dermatology Life Quality Index (DLQI) work/study domain (score = 3) at baseline. Presenteeism was assessed by summarizing mean changes in four Work Limitations Questionnaire (WLQ) domain scores at week 24. Analyses were compared between treatments and stratified by depression/anxiety status at baseline. Results: At week 24, 82.1% and 50.0% in the guselkumab and adalimumab groups, respectively, reported a DLQI work/study score = 0 (no effect of skin on work/study) ( p < .001). Mean changes (improvements) were greater in guselkumab-treated versus adalimumab-treated patients in the work limitations domains of Physical Demands (−6.9 vs. −3.3, p < .05), Mental-Interpersonal (−6.3 vs. −3.2, p < .06), and Output Demands (−6.2 vs. −2.2, p < .05). Improvements were consistent in patients with and without depression/anxiety. Conclusions: Psoriasis patients treated with guselkumab had significantly better improvements in absenteeism and presenteeism compared with those treated with adalimumab, regardless of depression/anxiety status.